2009
DOI: 10.1103/physrevb.79.205209
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance of magnetic semiconductor heterojunctions

Abstract: The giant magnetoresistance characteristics of magnetic III-V semiconductor p-n heterojunctions are described. The origin of the extremely large positive magnetoresistance ͑2680%͒ observed at room temperature and at a field of 18 T is attributed to efficient spin-polarized carrier transport. The magnetocurrent ratio of the junction saturates with magnetic field. The field dependence of the magnetoresistance points to the existence of a paramagnetic component, which determines the degree of spin polarization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…2,3 Furthermore, the MOVPE technique demonstrated that the films are ferromagnetic with a T c of 330 K. 3,4 The RudermannKittel-Kasuya-Yosida (RKKY) mechanism, where free holes mediate the ferromagnetism, is indeed favored in NGFS, while a small hole effective mass m h results in a long interaction distance and effective exchange coupling. The hole effective Bohr radius in NGFS suggests a large enough overlap with the Mn-induced hole wave functions to stabilize ferromagnetism even for small Mn contents.…”
Section: Narrow Gap Ferromagnetic Semiconductors (Ngfs) Such Asmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Furthermore, the MOVPE technique demonstrated that the films are ferromagnetic with a T c of 330 K. 3,4 The RudermannKittel-Kasuya-Yosida (RKKY) mechanism, where free holes mediate the ferromagnetism, is indeed favored in NGFS, while a small hole effective mass m h results in a long interaction distance and effective exchange coupling. The hole effective Bohr radius in NGFS suggests a large enough overlap with the Mn-induced hole wave functions to stabilize ferromagnetism even for small Mn contents.…”
Section: Narrow Gap Ferromagnetic Semiconductors (Ngfs) Such Asmentioning
confidence: 99%
“…5 The ferromagnetic states were measured using several techniques reported earlier. [2][3][4]6 In this work, several time-resolved differential transmission (TRDT) [7][8][9] schemes were employed to provide insight into the time scales and the nature of the interactions in MOVPE grown ferromagnetic InMnAs. We demonstrate the sensitivity and tunability of the carrier dynamics to the initial excitation region as well as the final states that are probed.…”
Section: Narrow Gap Ferromagnetic Semiconductors (Ngfs) Such Asmentioning
confidence: 99%
“…In the past, low temperature Molecular Beam Epitaxy(MBE) [1,2,10,11] techniques were nearly exclusively used to prepare NGFS; however, Metal-Organic Vapor Phase Epitaxy (MOVPE) demonstrated that a single phase NGFS compound could be deposited at 500 • C, much higher than that used in MBE [12][13][14]. Furthermore, the MOVPE technique demonstrated that the films are ferromagnetic with a T c above Room Tempera- * Author to whom correspondence should be addressed; Electronic address: khoda@vt.edu ture (RT) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the MOVPE technique demonstrated that the films are ferromagnetic with a T c above Room Tempera- * Author to whom correspondence should be addressed; Electronic address: khoda@vt.edu ture (RT) [12][13][14]. This is thought to be due to the fact that in MOVPE grown samples, there are local formations of Mn dimers, trimers and tetramers [15,16] which lowers the hole density and the Fermi Energy.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic mail: joseph.friedman@u-psud.fr. logic, 22,24,25 which we originally developed for InAs/InMnAs heterojunctions, 26 is applicable to any two-terminal magnetoresistive device that functions as a spin-diode. In this logic family, a constant bias voltage V bias is applied to all spin-diodes, and the current through each spin-diode is modulated by magnetic fields created by control wires.…”
mentioning
confidence: 99%